Viability of Bradyrhizobium japanicum on soybean seeds enhanced by magnetite nanoparticles during desiccation - Ghalamboran, M. R.; Ramsden, Jeremy J. (Cranfield University, 2010)
The aim of this study was to investigate whether magnetite nanoparticles affect the viability of Bradyrhizobium japanicum cells residing on the surface of soybean seeds during desiccation. Different concentrations of nanoparticles suspended in liquid medium, mixed with and adhering to Bradyrhizobium japanicum, were investigated at two temperatures, using both soybean seeds and glass beads as surrogates. Statistical design was a complete randomized block (CRB) in a factorial 6×2×2×6 experimental arrangement with four replications. The most important variable was the viability of Bradyrhizobium on the surface of the seeds. The nanoparticles increased Bradyrhizobium viability and inoculated seeds stored at low temperature had greater viability when nanoparticles had been added. At the optimum nanoparticle concentration, 50% bacterium viability on the seeds was retained after 5 days at 4ºC. Possible explanations for the observed effects are prop